Prasasti Plalangan: Data Waisnawa di Jawa - Ari Setyastuti; Rita M. Setianingsih (Balai Arkeologi Yogyakarta, 1994)
The Plalangan inscription was found in Plalangan Hamlet, Pendowoharjo Village, Sleman District, Sleman Regency. The inscription is carved on the thick side of the andesite stone which is square. The letters used are Old Javanese letters and Old Javanese language. Paleographically, the ten-line writing can be classified as writing around the 9th or 10th century AD. In the inscription it is also stated that worship of the God Vishnu is carried out by nine rama people in or from the Hastakarya area. The data on the inscriptions and reliefs found in Plalangan are interesting things to study. The data it contains can strengthen the notion that a Waisnawa sect or sect once existed in Java, especially in the Special Region of Yogyakarta.